2020
DOI: 10.24114/jg.v12i02.14474
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Konektivitas Dan Karakteristik Lorong Pada Sistem Hidrogeologi Mataair Beton, Kawasan Karst Gunungsewu, Kabupaten Gunungkidul Dengan Uji Perunutan

Abstract: Pemahaman tentang sistem hidrogeologi dan wilayah tangkapan air dari sebuah mata air sangatlah penting. Hal ini untuk membantu pengelolaan yang menjaga kelestariannya. Mataair Beton merupakan salah satu mataair yang memiliki peranan yang sangat penting di wilayah Ponjong, Kabupaten Gunungkidul. Suplai air dari mataair ini digunakan untuk memenuhi kebutuhan air bersih, irigasi persawahan dan perikanan. Penelitian ini bertujuan untuk mengetahui konektivitas dan karakterisasi lorong di sistem hidrogeologi Mataair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
2
6
0
1
Order By: Relevance
“…BTCs of the three locations formed three separate single curves with steep rising and falling limbs, indicating that the conduits developing along the underground rivers have large slope gradients. Similar results were found in the conduit of the Beton Karst Drainage Basin, which shares the same geological characteristics with this research, located at the transition between Semilir and Wonosari Formations and in the same hydrogeological subsystem (i.e., Ponjong Hydrogeological Subsystem) [16]. Single BTCs also indicate that the three locations have single conduits.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…BTCs of the three locations formed three separate single curves with steep rising and falling limbs, indicating that the conduits developing along the underground rivers have large slope gradients. Similar results were found in the conduit of the Beton Karst Drainage Basin, which shares the same geological characteristics with this research, located at the transition between Semilir and Wonosari Formations and in the same hydrogeological subsystem (i.e., Ponjong Hydrogeological Subsystem) [16]. Single BTCs also indicate that the three locations have single conduits.…”
Section: Resultssupporting
confidence: 87%
“…Cahyadi et al (2019; 2020) [15,16] divide the northern segment of the Ponjong Hydrogeological Subsystem into two karst drainage basins: Beton and Gremeng, but have not discussed it in detail. Therefore, the current research set out to complement previous studies that merely separated the subsystem's northern part from the Bribin Karst Drainage Basin.…”
Section: Introductionmentioning
confidence: 99%
“…This finding corresponds to Palmer [16,17], which explained that the underground tunnels influenced by allogenic rivers are generally single or in the form of caves with numerous branched passages (maze caves). The current research confirmed the artificial tracer test results conducted in the Seropan Ponor-Spring Beton system [15] and the cave passages in the upper course of the Gremeng KDB fed by the allogenic flows from the Panggung Masif Hills. The BTC presented in Figure 2 also showed connectivity between Jomblangan Cave and Beton Spring.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, it can be inferred that the groundwater flows from Sawah Ombo to Jomblangan Cave through a developed single conduit before it appears in Sriti Spring and flows as a surface river. The surface river then enters Seropan Ponor, which is connected to Beton Spring through a single large conduit [15]. The prediction of the flow from Pentung River to Beton Spring is presented in detail in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation